Comparison of Different Underlying Distributions in The Accelerated Failure Time (AFT) Model on Mortality of Covid-19 Patients - Meiza, Asti; Awaluddin, Asep Solih; Hidayah, Nurapni Oktapia; Taha, Adnan (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2022)
In 2022, the COVID-19 virus is still making headlines in various mass media because it is a virus that is very dangerous to health. The world health organization, WHO, explained that the virus caused a global pandemic that infected the whole world. The condition of a pandemic has not yet turned into an endemic. Based on the total confirmed COVID-19 positive cases, Indonesia ranks 18th in the world out of 222 infected countries. To determine the influence factors on COVID-19 cases, survival analysis is one of the techniques that could be applied. One of the most commonly used models in survival analysis is Accelerated Failure Time (AFT) model. In the AFT model, it is required to check assumptions regarding the feasibility of the distribution form. In this study, the distributions used are Weibull, Exponential, Log-normal, and Log-logistics distributions. We compare each distribution to get the best model to analyze death cases due to COVID-19. Comparisons are made by comparing the AIC values of each distribution. The best model is selected based on the smallest AIC value. The AFT model with a log-normal distribution is selected as the best model with an AIC value of 142.763. The AIC value for this log-normal distribution is the smallest compared to the AIC value for other distributions.Keywords: accelerated failure time model; COVID-19; mortality analysis; survival analysis. AbstrakTahun 2022, virus COVID-19 masih menjadi berita utama di berbagai media massa karena merupakan salah satu virus yang sangat berbahaya bagi kesehatan. Badan organisasi kesehatan dunia, WHO menjelaskan bahwa virus menyebabkan  terjadinya pandemi global yang menginfeksi seluruh dunia. Kondisi pandemi masih belum berubah menjadi endemi. Dari total yang terkonfirmasi positif COVID-19 Indonesia menduduki posisi ke-18 di dunia dari 222 negara yang terinfeksi. Untuk mengetahui faktor-faktor yang berpengaruh terhadap COVID-19 dan untuk menentukan model dari COVID-19 ini salah satunya dapat dilakukan dengan analisis survival. Salah satu model survival yang digunakan yaitu model Accelerated Failure Time (AFT).  Dalam model AFT ini diharuskan melakukan pengecekan asumsi-asumsi mengenai kelayakan bentuk distribusi. Pada penelitian ini distribusi yang digunakan yaitu distribusi Weibull, Eksponensial, Log-normal, dan Log-logistik. Dilakukan perbandingan antar tiap distribusi untuk mendapatkan model terbaik yang dapat digunakan dalam menganalisis kasus kematian akibat COVID-19. Perbandingan dilakukan dengan membandingkan nilai AIC dari  setiap distribusi. Hasil penelitian memilih model AFT dengan distribusi log-normal sebagai model terbaik dengan nilai AIC sebesar 142,763. Nilai AIC untuk distribusi log-normal ini paling kecil dibandingkan dengan nilai AIC untuk distribusi lainnya.Kata Kunci: analisis mortalitas; analisis survival; COVID-19; model accelerated failure time. 2020MSC: 62P10